Obtaining the Efficiency and Effectiveness of Fin in Unsteady State Conditions Using Explicit Finite Difference Method - Petrus Kanisius Purwadi; Budi Setyahandana; R.B.P. Harsilo (International Journal of Applied Sciences and Smart Technologies, 2021)
This paper discusses the search for fin efficiency and effectiveness in unsteady state conditions using numerical computation methods. The straight fin under review has a cross-sectional area that changes with the position x. The cross section of the fin is rectangular. The fins are composed of two different metal materials. The computation method used is the explicit finite difference methods. The properties of the fin material are assumed to be fixed, or do not change with changes in temperature. When the stability requirements are met, the use of the explicit finite difference methods yields satisfactory results. The use of the explicit finite difference methods can be developed for various other fin shapes, which are composed of two or more different materials, time-varying convection heat transfer coefficient, and the properties of the fin material that change with temperature.